(untitled) (Biodiversitas Journal of Biological Diversity, 2009)
Streptomyces spp 234P-16 producing xylanase was isolated from soil sample from Padang, West Sumatra, Indonesia. Crude enzyme (produced by centrifuging the culture at 14000 rpm for about 5 minutes) and purified xylanase have an optimum condition at pH 5 and 90oC. Crude xylanase have half life time of 4 hours, whereas purified xylanase have half life time of 2.5 hours at 90oC. The molecular mass of purified xylanase was determined to be 42.4 kDa. The Arabinofuranosidase have a Km and Vmax value of 1.98 mg/mL and 523 Î¼mol/minute/mg, respectively Key words: xylanase, xylooligosaccharide, arabinofuranosidase, Streptomyces.